Theoretical Computer Science 6th IFIP TC 1/WG 2.2 International Conference, TCS 2010, Held as Part of WCC 2010, Brisbane, Australia, September 20-23, 2010. Proceedings - Calude, Cristian S.; Sassone, Vladimiro. (IFIP Advances in Information and Communication Technology,, 2010)
This book constitutes the refereed proceedings of the 6th FIP WG 2.2 International Conference, TCS 2010, held as a part of the 21th World Computer Congress, WCC 2010, in Brisbane, Australia, in September 2010. The 23 revised full papers presented, together with 4 invited talks, were carefully reviewed and selected from 39 submissions. TCS 2010 deals with topics focused at but not limited to algorithms, complexity, models of computation, logic, semantics, specification and verification, power-awareness issues in wireless networks, data mining, knowledge discovery, multiprocessor issues as well as AI issues.